Observational analysis of cumulus and stratocumulus entrainment using ozone - Weaver, Clark Jay, author; Pearson, Richard, Jr., author (Colorado State University. Libraries, 1987)
This study demonstrates that ozone mixing ratio (03) is conserved during moist convection and can be used as a tracer for cloud entrainment studies. The approach in Part I is to apply mixing line analysis to pairs of Oe, 01, total water mixing ratio and 03 derived from aircraft penetrations of growing cumulus congestus. Conclusions about entrainment from the mixing diagrams employing 03 agree with those using thermodynamic quantities. Any disagreement uncovered deficiencies in the water substance measurement technique. Ozone is conserved / and recommended for future entrainments studies. Other conclusions were that strong updrafts, thought to be a diluted adiabatic core, entrained laterally from the environment at the observation level. In contrast, the downshear region of the cloud entrained air from above the observation level as well as laterally. Entrainment instability is thought to be a cause of stratocumulus break up. At the cloud-overlying air interface, mixtures may form which are negatively buoyant due to cloud droplet evaporation. In Part II, quantities devised to predict breakup, ~ 2 , X and ~m, are obtained from aircraft observations and are tested against cloud observations from satellite. Often, the parameters indicate that breakup should occur but the clouds remain, sometimes for several days. One possible explanation for break up is vertical motion from passing synoptic cyclones. Several cases suggest that break up is associated with the downward vertical motion from the cold air advection behind a eastward moving cyclone.
October 1987.
Also issued as Clark Jay Weaver's dissertation (Ph.D.) -- Colorado State University, 1987.
Keywords: Clouds -- Observations; Convection (Meteorology); Atmospheric ozone